Relationships between implicit motives, self-attributed motives, and personal goal commitments - Rawolle, Maika; Schultheiss, Maria; Schultheiss, Oliver C. (Frontiers in Psychology, 2013)
This research examined the relationships between measures of the implicit and the explicit motivational systems. We analyzed the relationships between picture-story measures of implicit motives, questionnaire measures of self-attributed motives, and ideographically assessed personal goal commitments within the domains achievement, affiliation, and power through a reanalysis of three data sets from the USA and Germany (total N = 309). No significant positive within-domain correlations of implicit motives with self-attributed motives or personal goal commitments were found, and self-attributed motives correlated substantially and positively with personal goals. Results did not systematically differ between data sets.